Soil Test Based Fertilizer Recommendation for C1usterbean in Torripsamments of Rajasthan - Gulati, I J; Yadav, S R; Singh, S P (Annals of Arid Zone, 2016)
Soil t st crop response correlation studies’were conducted with clusterbean (val’. RGC-986) in Torripsamments of Rajasthan during kharif200 I. Fertilizer adjustment equations were formulated for clusterbean following Ramamoorthy’s inductive-cumtargeted yield model. The nutrient requirement for producing one quintal of c.lusterbean was found to be 7.16, 1.10 and 3.70 kg of N. P20S, and K20, respectIvely. The per cent nutrient utilization efficiencies frori1 soil and fertilizer nutrients were found to be 45.98 and 69.11 for N, 53.72 and 51.87 for P20S and51.17 and 40.21 for K20, respectively. Fertilizer adjustment equations fommlated for clusterbeanwere verified by conducting follow-up trials. In STCR technology, the fertilizer d ses are tailored to the requirements of specific yield targets of clusterbean takmg mto account the contribution from soil and fertilizers ..